EXPRESSION OF CASPASE 3 IN RAT LIVER CELLS BY MAXIMUM PHYSICAL EXERCISE AFTER ADMINISTRATION OF GAGATAN HARIMAU NANOHERBAL (Paraboea leuserensis B.L.Burtt) - ashfira; Syafruddin Ilyas; Masitta Tanjung (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
This research aims to analyse Expression of Caspase 3 in Rat Liver Cells With Maximum Physical Exercise After Administration of Gagatan Harimau Nanoherbal (Paraboea leuserensis B.L.Burtt). The research was conducted in April-June 2023. The research location was the Animal Physiology Laboratory and Experimental Animal House, Department of Biology, FMIPA USU, PT. Synergy of Indonesian Nanotech, South Tangerang, Banten and the Anatomic Pathology Laboratory, Faculty of Medicine, University of North Sumatra, Medan. There were 6 treatments in the study, namely control group (K-), maximum physical exercise (K+), maximum physical exercise + Vitamin C at a dose of 2 mg/Kg Body Weight (P1), maximum physical exercise + Gagatan Harimau nanoherbal 100 mg/Kg BW (P2 ), Maximum physical exercise + Gagatan Harimau nanoherbal dose 125 mg/Kg BW (P3), Maximum physical exercise + Gagatan Harimau nanoherbal dose 150 mg/Kg BW (P4). The data obtained from each observation parameter (variable) is recorded and presented in table form. The data was then analyzed using SPSS version 25 software with significant differences determined at p<0.05. The results of the study showed significant differences between all groups (p<0.05) in the expression of caspase 3 in the liver. A dose of 150 mg/Kg BW from the nanoherbal Gagatan Harimau leaves (Paraboea leuserensis B.L.Burtt) reduced the expression of caspase 3 in rat liver. The induction of gagatan harimau leaf nanoherbal to act as an antioxidant in male rats given swimming physical training showed improvements in liver histology and morphology. The dose of 150 mg/KgBW of nanoherbal gagatan harimau leaves was the best dose because it showed cell regeneration that was close to the normal treatment group.